2008
DOI: 10.1530/rep-07-0423
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-dependent modulation of anti-Müllerian hormone in female Siberian hamsters, Phodopus sungorus

Abstract: Fertility and fecundity decline with advancing age in female mammals, but reproductive aging was decelerated in Siberian hamsters (Phodopus sungorus) raised in a short-day (SD) photoperiod. Litter success was significantly improved in older hamsters when reared in SD and the number of primordial follicles was twice that of females held in long days (LD). Because anti-Mü llerian hormone (AMH) appears to inhibit the recruitment of primordial follicles in mice, we sought to determine whether the expression patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…Lastly, as described previously, ovarian AMH protein concentrations are threefold higher in SD than in LD hamsters, likely due to the broader distribution of AMH-expressing cells (Kabithe & Place 2008). Previous studies have shown that AMH reduces follicle sensitivity to FSH via reductions in FSH receptor expression in granulosa cells and the inhibition of FSH-stimulated aromatase activity (Pellatt et al 2007).…”
Section: Long-term Rhfsh Supplementation In Sdssupporting
confidence: 53%
See 4 more Smart Citations
“…Lastly, as described previously, ovarian AMH protein concentrations are threefold higher in SD than in LD hamsters, likely due to the broader distribution of AMH-expressing cells (Kabithe & Place 2008). Previous studies have shown that AMH reduces follicle sensitivity to FSH via reductions in FSH receptor expression in granulosa cells and the inhibition of FSH-stimulated aromatase activity (Pellatt et al 2007).…”
Section: Long-term Rhfsh Supplementation In Sdssupporting
confidence: 53%
“…Interestingly, although high concentrations of AMH immunoreactive HGCs were observed in the ovaries of SD controls, no differences in Amh mRNA were observed among any of the groups. Western blots have shown that AMH protein levels were threefold higher in SD ovaries compared with LD ovaries at 10 weeks of age (Kabithe & Place et al 2008). However, this study is the first to examine SD-induced changes in Amh mRNA.…”
Section: Gonadotropin Suppression In Ldsmentioning
confidence: 75%
See 3 more Smart Citations